Editorial: Psychological frailty in aging: Lifespan trajectories and emerging risks - Navarro-Pardo, E.; Bobrowicz-Campos, E.; Facal, D. (Frontiers in Psychology, 2022)
In the study of aging, “frailty” is the state that increases the individual’s vulnerability to stress factors. In the context of biomedical sciences, the concept of frailty has been operationalized differently, and the most used is the frailty phenotype. However, different constructs have emerged in recent decades complementing the traditional one of physical frailty. From a biopsychosocial, gerontological outlook, multidimensional and dynamic perspectives that include physical, functional, cognitive, and psychosocial domains (e.g., cumulative deficit model), are currently more relevant (Rockwood and Mitnitski, 2007; Gobbens et al., 2010).